LARVICIDAL ACTIVITY OF KEMUNING LEAF EXTRACT ( Murraya Paniculata (L.) Jack ) AGAINST DENGUE HEMORRHAGIC FEVER VECTOR - Putri, Aini (Majority, 2015)
Dengue hemorrhagic fever (DHF) is an infectious disease caused by the dengue virus and is transmitted through the bite of Ae. aegypti. Kemuning leaves (Murraya paniculata (L.) Jack) can be used as a natural larvicidal with its secondary metabolites. Writing these articles aimed to know the metabolite secondary found in extract kemuning and effectiveness as larvasida Ae.aegypti using literature as a source of data search. After testing of bioactive compounds in the kemuning leaves alkaloid obtained positive test indicates the presence of an orange precipitate with Dragendorff reagent. Saponins and tannins test positive with the foam while shaking using distilled water and MgSO4, sianidin test showed positive flavonoids with red crystal picture. Kemuning leaves contain secondary metabolites are alkaloids, saponins, tannins, and flavonoids. At myrtle extract using ethanol and ethyl acetate obtained larval mortality at 9000 bpj concentration of 1000 ppm and the number of dead larvae are 94% and 12%.Extract ethanol leaves kemuning more gave impacts against larvasida Ae. aegypti mosquito compared with an extract of ethyl acetate leaves kemuning due to the activity of polarity against a metabolite secondary leaves kemuning. Keywords : dengue hemorrhagic fever, larvasida, Murraya paniculata (L) Jack Abstrak Penyakit demam berdarah dengue (DBD) adalah penyakit menular yang disebabkan oleh virus dengue dan ditularkan melalui gigitan nyamuk Ae. aegypti.Daun kemuning (Murraya paniculata (L) Jack) dapat digunakan sebagai larvasida alami dengan metabolit sekunder yang dimilikinya. Penulisan artikel ini bertujuan untuk mengetahui kandungan metabolit sekunder yang terdapat pada kemuning danefektifitasekstrak kemuningsebagai larvasidaAedes aegyptidengan menggunakan metode penelusuran kepustakaan sebagai sumber datanya. Setelah dilakukan uji senyawa bioaktif pada daun kemuning didapatkanuji alkaloid positifmenunjukkan adanya endapan warna jingga dengan reagen Dragendorff. Uji saponin dan tannin positif dengan adanya busa saat pengocokan menggunakan aquadest dan Mgso4, uji sianidin menunjukkan flavonoid positif dengan gambaran kristal merah. Daun kemuning mengandung metabolit sekunder yaitu alkaloid, saponin, tannin, dan flavonoid.Pada hasil ekstrak kemuning menggunakan pelarut etanol dan etil asetat didapatkan kematian larva pada konsentrasi 9000 bpj dan 1000 ppm dengan jumlah larva mati masing-masing sebanyak 94% dan 12%. Ekstrak etanol daun kemuning memiliki efektifitas lebih baik terhadap larvasida Ae. aegypti dibandingkan dengan ekstrak etil asetat daun kemuning akibat kepolaritasannya terhadap metabolit sekunder daun kemuning. Kata kunci : demam berdarah dengue, larvasida, Murraya paniculata (L) Jack